Penghormatan Ze Hai Zhen Ren - Dewa Tionghoa Di Tekhai Bio: 澤海真人崇拜-澤海廟的印華神 - Ardian Cangianto; C. Dewi Hartati (Parahyangan Catholic University, 2021)
The events of 1740 in Batavia brought the Chinese community into a new phase. One of the new chapters that has never been studied is the birth of local gods who are worshiped in various temples. The gods were none other than the Chinese folk he- roes who fought against the Dutch colonialism. Among them are Yiyong gong (義勇公) which is worshiped in the city of Lasem and Zehai zhenren (澤海真人) in various cities in Central Java, such as in the cities of Tegal, Semarang and Pekalongan. The cult of Zehai zenren is wider than the cult of Yiyonggong, even in some circles the Javanese community also respects the figure of Zehai zenren. Zehai zenren can be respected among the Javanese people, especially those who become fishermen because they believe that Zehai zenren is the ‘god’ protecting sailors and traders. In addition to its distribution in Central Java, it turned out that based on field research, it was found that there were Chinese people living in the West Java area who worshiped Zehai zenren as their patron god. That there are local Chinese heroes who can be worshiped whose distribution is wider than the local Chinese Indonesian gods deserves to be investigated. It should also be noted that Zehai zhenren's ‘bodyguards’ are Javanese. Belief in Zehai zhenren that transcends ethnic boundaries can occur because of the closeness of the belief system of the people of Central Java or known as Kejawen with the Chinese belief system. His beliefs are inclusive, build harmony and respect for people who are worthy of respect.